Diverse supramolecular structures formed by self‐assembling proteins of the B acillus subtilis spore coat - Jiang, Shuo (Mol Microbiol, 2015)
Bacterial spores (endospores), such as those of the pathogens C lostridium difficile and B acillus anthracis, are uniquely stable cell forms, highly resistant to harsh environmental insults. B acillus subtilis is the best studied spore‐former and we have used it to address the question of how the spore coat is assembled from multiple components to form a robust, protective superstructure. B . subtilis coat proteins (CotY, CotE, CotV and CotW) expressed in E scherichia coli can arrange intracellularly into highly stable macro‐structures through processes of self‐assembly. Using electron microscopy, we demonstrate the capacity of these proteins to generate ordered one‐dimensional fibres, two‐dimensional sheets and three‐dimensional stacks. In one case (CotY), the high degree of order favours strong, cooperative intracellular disulfide cross‐linking. Assemblies of this kind could form exquisitely adapted building blocks for higher‐order assembly across all spore‐formers. These physically robust arrayed units could also have novel applications in nano‐biotechnology processes.